Beyond information seeking: a general model of information behaviour. - Natalya Godbold (Information Research: An International Electronic Journal)
Introduction. The aim of the paper is to review models of information behaviour and to propose new models that extend the concept beyond simply information seeking to consider other modes of behaviour. The models chiefly explored are those of Wilson and Dervin. Argument A shortcoming of some models of information behaviour is that they present a sequence of stages in that behaviour and it is evident that actual behaviour is not always explained effectively by stages in a sequence. Development. A model of 'multi-directionality' is explored, to overcome the notion of sequential stages and, using Dervin's concept of 'the gap', modes of information behaviour are developed that include, for example, creating, destroying and avoiding information as well as seeking it. Conclusion. New models of information behaviour are presented that: replace the notion of 'barriers' with the concept of 'gap', as a means of integrating the views of Wilson and Dervin; incorporate the notion of multi-directionality; and identify ways in which an individual may navigate 'the gap' using different modes of information behaviour.